The Augmented Reality (AR) Based on Artificial Intellegence (AI) in Integrated Marketing Communication (IMC) in Tourism Villages - Setiawan, Budi (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
This study examines the implementation of Augmented Reality (AR) based on Artificial Intelligence (AI) in Integrated Marketing Communication (IMC) in tourism villages, driven by the need for advanced technology to sustain the attractiveness of tourist destinations. The main objectives are to explore the potential of AR and AI technologies in enhancing tourist experiences, identify best practices in IMC, and analyze economic and environmental impacts. A literature review approach was used to gather findings from recent studies, indicating that AR provides deeper and more informative interactive experiences, while AI enables personalized experiences tailored to individual tourist preferences. The research methodology involved critical analysis of relevant literature, including case studies from several tourism villages in Indonesia and abroad that have successfully implemented these technologies. The results indicate that the implementation of AR and AI can significantly enhance destination attractiveness, strengthen branding, and support sustainable tourism development through better environmental management and more active involvement of local communities. However, challenges such as implementation costs, data privacy, and technological dependency need to be considered. This research provides a foundation for developing effective integrated marketing strategies using AR and AI, meeting the needs of modern tourists who increasingly demand informative, interactive, and sustainable experiences.